Encyclopedia of race and crime - Greene, Helen Taylor, 1949-; Gabbidon, Shaun L., 1967-; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2009)
Comprehensive in nature, these two volumes cover a number of broad thematic areas including basic concepts and theories of criminal justice, juvenile justice, public policy, the media specific groups and populations, and much more.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Crime and race -- United States -- Encyclopedias; Criminal justice, Administration of -- United States -- Encyclopedias; Discrimination in criminal justice administration -- United States -- Encyclopedias; Minorities -- United States -- Encyclopedias; Electronic books